Quantification of health-related quality of life among patients with rheumatoid arthritis: An institution-based study in Kolkata, West Bengal - Mandal, Moumita; Dasgupta, Aparajita; Dutt, Debashis; Taraphdar, Pranita; Ghosh, Parasar; Paul, Bobby (Journal of family medicine and primary care, 2020)
Context: Rheumatoid arthritis (RA) is a known chronic debilitating disease accounting for a large percentage of disability globally. Pain and stiffness, decreased work function, depression and emotional state alteration, fatigue, disability, and social handicaps are some patient reported outcomes, which if considered with priority the health-related quality of life (HRQOL) of patients with RA could improve. Aims: This study was conducted with the aim to assess the HRQOL of the patients with RA and the determinants related to it. Settings and Design: This was a cross-sectional study conducted at Rheumatology Department of a tertiary care hospital, Kolkata. Subjects and Methods: A total of 252 patients with RA were selected in this study through systematic random sampling. Statistical Analysis Used: Data were analyzed using appropriate statistical measures with Statistical Package for the Social Sciences(SPSS) version 16.0 (Armonk, NY: IBM Corporation) software program, version 16.0. Univariate and multivariable logistic regression were carried out. Results: In the study, the mean age of the patients was 43.1 years (mean age ±SD: 43.05±10.63 years). The proportion of female subjects was 84.5%. Unsatisfactory QOL was found in 59.9% study participants. In multivariable logistic regression unsatisfactory quality of life was significantly associated to moderate to high functional disability [AOR: 6.04, CI: 2.86, 12.78], disease activity moderate to high [AOR: 5.41, CI: 1.87, 15.69], presence of comorbidity [AOR: 2.90, CI: 1.39, 6.04], extra-articular manifestations [AOR: 3.14, CI: 1.41, 6.96] and delay in starting Disease-Modifying Anti-Rheumatoid Drugs (DMARDs) [AOR: 1.24, CI: 1.08, 1.42]. Conclusion: Findings of this study clearly indicate the presence of high proportion of unsatisfactory QOL among the patients with RA. Early identification and prompt referral are the key strategies to prevent any permanent damage. Regular follow-up of the patients should be carried out to prevent or delay the disability progression and provide high-quality physical and mental health.